2019
DOI: 10.1103/physrevresearch.1.033172
|View full text |Cite
|
Sign up to set email alerts
|

Transport in disordered systems: The single big jump approach

Abstract: In a growing number of strongly disordered and dense systems, the dynamics of a particle pulled by an external force field exhibits superdiffusion. In the context of glass-forming systems, supercooled glasses, and contamination spreading in porous media, it was suggested that this behavior be modeled with a biased continuous-time random walk. Here we analyze the plume of particles lagging far behind the mean, with the single big jump principle. Revealing the mechanism of the anomaly, we show how a single trapp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 56 publications
(122 reference statements)
0
19
0
Order By: Relevance
“… If the jump length PDF is sub-exponential, the far tail of will deviate from what we found here. Most likely the principle of the single big jump [ 64 , 65 , 66 ] will hold in some form, but the details of the theory are left unknown. Recently Dechant et al showed how the CTRW picture emerges from an under-damped Langevin description of a particle in a periodic potential [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“… If the jump length PDF is sub-exponential, the far tail of will deviate from what we found here. Most likely the principle of the single big jump [ 64 , 65 , 66 ] will hold in some form, but the details of the theory are left unknown. Recently Dechant et al showed how the CTRW picture emerges from an under-damped Langevin description of a particle in a periodic potential [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, so far, the Scher-Berkowitz theoretical framework is based on a random walk picture [30] and not on a governing fractional advection-diffusion equation. Both the CTRW and the BSMW frameworks and the experiments in the field agree on one thing: advection-diffusion is anomalous and non-symmetric [31,34], however otherwise these schools promote widely different philosophies.…”
mentioning
confidence: 88%
“…This section draws on extreme value statistics. We refer the reader to [25][26][27] for an introduction to extreme value statistics and applications in statistical mechanics, and we mention [28] as an example of recent work which uses extreme value statistics as a tool to analyse stochastic models for dispersion. We have seen that when D is small the integrals defining the mean first passage time are approximated by sums over extrema of the potential, as described by equation (17).…”
Section: Statistics Of Extreme-weighted Sumsmentioning
confidence: 99%